The Effects of Fish Oil on Cardiovascular Diseases: Systematical Evaluation and Recent Advance - Liao, Jia; Xiong, Qingsong; Yin, Yuehui; Ling, Zhiyu; Chen, Shaojie (Frontiers in Cardiovascular Medicine, 2022)
Fish oil is rich in unsaturated fatty acids, i.e. eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), both of which are widely distributed in the body such as heart and brain. In vivo and in vitro experiments showed that unsaturated fatty acids may have effects of anti-inflammation, anti-oxidation, protecting vascular endothelial cells, modifying autonomic nerve function, regulating blood lipid and thrombosis inhibition. Given the relevance to the public health, there has been increasing interest in the research of potential cardioprotective effects of the fish oil. Accumulated evidence showed that fish oil supplementation may reduce the risk of cardiovascular events and in specific it may have potential benefit in improving the prognosis of patients with hypertension, coronary heart disease, cardiac arrhythmias or heart failure; however some studies yielded inconsistent results. In this article, we performed an updated systematical review in order to provide a contemporary understanding with regard to the effects of fish oil on cardiovascular diseases.